Preliminary evaluation and nutritional properties of Spondias mombin L. fruits from different native plants (Research, Society and Development, 2020)
The cajá fruit stands out for its peculiar flavor, but little is known about its physical, physical-chemical and nutritional characteristics. The knowledge of fruit and seed biometrics, physicochemical and nutritional composition provides information for the conservation and exploitation of resources of economic value, and can be exploited by genetic improvement programs to obtain cultivars that provide fruits with important characteristics for commercialization. Thus, it aimed to evaluate the characteristics we sought to evaluate these characteristics considering samples from different trees / regions of the municipality of  Montes Claros of Goiás. The cajá fruit biometry (density, volume, mass, fruit and seed size and pulp yield) was measured. Titratable acidity, soluble solids content, pH, vitamin C content and mineral content were also measured. Total phenolic compounds and antioxidant activity were evaluated by the Folin-Ciocalteau, ORAC and ABTS methods, respectively. With the results obtained, it was possible to infer that the fruits harvested in different trees of different places differed statistically. The fruits of Region 2 had the highest fruit and seed length and diameter, as well as the highest pulp thickness, macro and micronutrient content and total phenolic compounds content, compared to fruit from other areas probably influenced by type of soil. The knowledge of the characteristics of the fruits from different trees / regions is necessary because the industrialization needs parameters for standardization in the formulation of different foods.